Physiological relevance of plant 2‐Cys peroxiredoxin overoxidation level and oligomerization status. (14th November 2015) - Cerveau, Delphine; Ouahrani, Djelloul; Marok, Mohamed Amine; Blanchard, Laurence; Rey, Pascal
Abstract: Peroxiredoxins are ubiquitous thioredoxin‐dependent peroxidases presumed to display, upon environmental constraints, a chaperone function resulting from a redox‐dependent conformational switch. In this work, using biochemical and genetic approaches, we aimed to unravel the factors regulating the redox status and the conformation of the plastidial 2‐Cys peroxiredoxin (2‐Cys PRX) in plants. In Arabidopsis, we show that in optimal growth conditions, the overoxidation level mainly depends on the availability of thioredoxin‐related electron donors, but not on sulfiredoxin, the enzyme reducing the 2‐Cys PRX overoxidized form. We also observed that upon various physiological temperature, osmotic and light stress conditions, the overoxidation level and oligomerization status of 2‐Cys PRX can moderately vary depending on the constraint type. Further, no major change was noticed regarding protein conformation in water‐stressed Arabidopsis, barley and potato plants, whereas species‐dependent up‐ and down‐variations in overoxidation were observed. In contrast, both 2‐Cys PRX overoxidation and oligomerization were strongly induced during a severe oxidative stress generated by methyl viologen. From these data, revealing that the oligomerization status of plant 2‐Cys PRX does not exhibit important variation and is not tightly linked to the protein redox status upon physiologically relevant environmental constraints, the possible in planta functions of 2‐Cys PRX are discussed. Abstract : Environmental stress conditions are presumed to trigger both overoxidation and oligomerization of plant 2‐Cys peroxiredoxin (PRX), thus conferring a chaperone role to this thiol peroxidase. In this work, we showed that the 2‐Cys PRX overoxidation is mainly regulated by thioredoxin‐like electron donors in optimal growth conditions and by sulfiredoxin upon environmental constraints. Physiologically relevant stress conditions did not lead to concomitant and noticeable modifications in 2‐Cys PRX overoxidation and oligomerization in Arabidopsis, potato and barley unlike severe oxidative stress induced by methyl viologen. These data lead us to discuss the 2‐Cys PRX roles in higher plants under physiological environmental constraints.